2012
DOI: 10.1016/j.vetmic.2011.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel Bartonella spp. in bats and evidence of Asian gray shrew as a new potential reservoir of Bartonella

Abstract: Many studies indicated that small mammals are important reservoirs for Bartonella species. Using molecular methods, several studies have documented that bats could harbor Bartonella. This study was conducted to investigate the relationship of Bartonella spp. identified in bats and small mammals living in the same ecological environment. During May 2009 and March 2010, a total of 102 blood specimens were collected. By whole blood culture and molecular identification, a total of 6 bats, 1 rodent and 9 shrews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 36 publications
1
48
0
1
Order By: Relevance
“…In our study, the prevalence of Bartonella-infected bats (13.6%-8/59) is greater than that described in Taiwan (11.1%-6/54), but less than those reported in Peru (24.1%-27/112), Kenya (30.2%-106/331), Guatemala (33%-39/ 118), Costa Rica (33.3%), Vietnam (35%-21/60), and Finland (37%-46/124) (Kosoy et al 2010, Bai et al 2011, Lin et al 2012, Anh et al 2015, Judson et al 2015, Lilley et al 2015). It appears that bacteremia is common in bats and depending on the species Bartonella spp.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In our study, the prevalence of Bartonella-infected bats (13.6%-8/59) is greater than that described in Taiwan (11.1%-6/54), but less than those reported in Peru (24.1%-27/112), Kenya (30.2%-106/331), Guatemala (33%-39/ 118), Costa Rica (33.3%), Vietnam (35%-21/60), and Finland (37%-46/124) (Kosoy et al 2010, Bai et al 2011, Lin et al 2012, Anh et al 2015, Judson et al 2015, Lilley et al 2015). It appears that bacteremia is common in bats and depending on the species Bartonella spp.…”
Section: Discussionmentioning
confidence: 59%
“…Many blood-sucking arthropods (fleas, ticks, lice, and sand flies) are involved in the transmission of bartonelloses, which are emerging diseases (La Scola et al 2003). Bartonella infections in bats have already been described in the United Kingdom, Finland, Kenya, Nigeria, Costa Rica, Guatemala, Peru, Taiwan, and Vietnam (Concannon et al 2005, Kosoy et al 2010, Bai et al 2011, Lin et al 2012, Veikkolainen et al 2014, Kamani et al 2014, Anh et al 2015, Judson et al 2015, Lilley et al 2015, although their role in human and animal pathology still remain unclear. Many strains isolated from bats all over the world are genetically distant and may represent new species.…”
Section: Introductionmentioning
confidence: 99%
“…Of the more than 30 described Bartonella species, around half have been identified as human pathogens causing a range of illnesses from mild fever to potentially fatal endocarditis (Breitschwerdt et al, 2010; Chomel and Kasten, 2010). Numerous studies have demonstrated that bats and their ectoparasites show a high prevalence and genetic diversity of bartonella bacteria (Anh et al, 2015; Bai et al, 2015, 2012, 2011; Brook et al, 2015; Concannon et al, 2005; Judson et al, 2015; Kamani et al, 2014; Kosoy et al, 2010; Lin et al, 2012; Olival et al, 2015; Reeves et al, 2007, 2005; Veikkolainen et al, 2014). Recently, bats have been implicated in potential spillover of bartonellae into dogs (Bai et al, 2010; Lin et al, 2012) and a single human case (Lin et al, 2010; Veikkolainen et al, 2014), although the role of bats as sources of zoonotic bartonellosis is still unclear (Mannerings et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nycteribiids are known to host a wide variety of Bartonella spp. (10), and contrasting patterns of Bartonella-bat host associations have been described across Africa (8,9,22), South America (23)(24)(25), Europe (26), and Asia (27).…”
mentioning
confidence: 99%